2012
DOI: 10.7451/cbe.2012.54.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Measured and predicted temperatures in a grain processing building under heat treatment – 1. Temperature profiles during heat treatment

Abstract: Temperature gradients in the vertical direction decreased with increasing height. The maximum and mean temperature gradients above the surface of the concrete floor, in the absence of grain, were 5.4°C/cm and 3.6±0.0°C/cm; respectively. The room temperatures at higher locations varied less than those at lower locations. Moreover, after the surface grain temperature reached 97% of its maximum temperature, it was influenced by the local temperature and periphery configuration. Key words: Heat treatment, grain-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The measured temperatures (Jian et al 2012) at the concrete surface, middle of the grain piles or tubes, and the surface of the grain mass were compared with the temperatures predicted by the developed models. The residues between measured and predicted temperatures were used to verify and validate the developed models.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The measured temperatures (Jian et al 2012) at the concrete surface, middle of the grain piles or tubes, and the surface of the grain mass were compared with the temperatures predicted by the developed models. The residues between measured and predicted temperatures were used to verify and validate the developed models.…”
Section: Discussionmentioning
confidence: 99%
“…Brijwani et al (2010) also found that floors covered with 0.02 m deep flour took 1 to 5 h longer to reach 50°C than floors with thin flour dust. The setup of the experiment was slightly different than that used in this experiment (Jian et al 2012). The former had the flour inside a plastic box with a lid.…”
Section: Grain Temperaturesmentioning
confidence: 99%
See 3 more Smart Citations